DEVELOPMENT OF HALAL TOURISM POTENTIAL AND PARTICIPATION OF THE ULAMA DEVELOPMENTAL ASSEMBLY (MPU) IN A PUBLIC ADMINISTRATION PERSPECTIVE - Payumi, Payumi; Hajar, Siti; Bida, Obed (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
The development of halal tourism potential has become a strategic issue and main focus in efforts to attract tourism attractions in various destinations, including Gayo Lues Regency. From a public administration perspective, the role of the Ulama Consultative Council (MPU) is very important in directing and ensuring that the development of halal tourism is in accordance with local religious and cultural values. The aim of this research is to determine MPU participation which can influence the development of halal tourism potential from a public administration perspective. The method used in this research is a qualitative analysis approach. The research results show that MPU's active participation in the development of halal tourism is by contributing to decision making that takes into account local religious and cultural values, even though a specific policy regarding halal tourism in Gayo Lues Regency has not yet been formulated. Apart from that, in making decisions, the MPU also participates in promoting and socializing tourism development in Gayo Lues Regency, playing a mediator role between the government, industry players and the community in an effort to create an environment that supports the development of halal tourism.Pengembangan potensi wisata halal telah menjadi isu strategis dan fokus utama dalam upaya menarik daya tarik pariwisata di berbagai destinasi, termasuk Kabupaten Gayo Lues. Dalam perspektif administrasi publik, peran Majelis Permusyawaratan Ulama (MPU) menjadi sangat penting dalam mengarahkan dan memastikan bahwa pengembangan wisata halal sesuai dengan nilai-nilai keagamaan dan budaya setempat. Tujuan penelitian ini untuk mengetahui partisipasi MPU yang dapat mempengaruhi pengembangan potensi wisata halal dalam perspektif administrasi publik. Metode yang digunakan dalam penelitian ini adalah pendekatan analisis kualitatif. Hasil penelitian menunjukkan bahwa partisipasi aktif MPU dalam pengembangan wisata halal dengan memberikan kontribusi terhadap pengambilan keputusan yang mempertimbangkan nilai-nilai keagamaan dan budaya setempat, walaupun kebijakan khusus tentang pariwisata halal di Kabupaten Gayo Lues belum tersusun. Selain, dalam pengambilan keputusan maka MPU juga ikut dalam mempromosikan dan mensosialisasikan tentang pengembangan pariwisata di Kabupaten Gayo Lues yang berperan mediator antara pemerintah, pelaku industri dan masyarakat dalam upaya menciptakan lingkungan yang mendukung pengembangan wisata halal.